Formal education vs. informal education in the Roma community—a silent confrontation where nobody wins - Herțanu, Margareta; Soponaru, Camelia; Păduraru, Ancuța E. (Frontiers in Education, 2023)
Objectives Our main aim was to identify the advantages and disadvantages that the Roma relate to formal education vs. informal education, a discrepancy in the balance between the two can enrich the explanations regarding their low level of schooling—which hinders their social inclusion. Method There were 28 participants of Roma ethnicity, aged between 19 and 52 years old, who took part in the study: 15 were married, 13 were single, all of them school graduates. The design of the study is a qualitative one and the data was collected by means of three focus groups, based on a semi-structured interview. The data was analysed by using the method of content analysis. Results In addition to the disadvantages related to institutional and economic factors, the Roma encounter in schools that belong to the cultural majority difficulties related to language and a lack of elements belonging to their culture. While they get used to the culture of the majority, they feel that they lose their own identity and that they are silently excluded from their community. Conclusion Formal education is seen as a way of personal development and as a path to an advantageous job, a door of access to the majority culture. However, informal education seems to win all the time, as a result of the family sovereignty and the fact that it is the central factor in the transmission and preservation of the Roma culture.